Content Alignment Project Report. English Language Arts, Mathematics, and Social Studies. Alignment of Community College, University, and Internship Content - Mayo, Nolie; Houston-Clear Lake Univ., TX. School of Education ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
A Content Alignment Committee defined the subject matter that beginning teachers who complete the University of Houston-Clear Lake (UHCL) program must understand in order to provide meaningful learning experiences to public school students. The committee met during 1997 to examine content standards in English/language arts, mathematics, and social studies. Each of the three action teams included someone from the School of Education, the UHCL school housing the discipline where the content courses were taught, a community college, and a professional development school. The three teams developed topics or concept statements that included knowledge, central themes, and patterns of thinking specific to the content. The content statements were aligned with national, state, and local standards identified as an appropriate emphasis in the teacher preparation program at the community college, university, or professional development school. This paper describes content alignment project objectives, the project concept and vision statement, the background of teacher education standards, and the project review process. The resulting standards for each of the three areas are included. An appendix presents the University of Houston-Clear Lake Community College Transfer Plans and a list of required courses in each content area. (SM)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College School Cooperation; Community Colleges; Elementary Secondary Education; English Curriculum; Higher Education; Language Arts; Mathematics Education; National Standards; Partnerships in Education; Preservice Teacher Education; Public Schools; Social Studies; State Standards; Teacher Certification; Teacher Competencies; University of Houston Clear Lake TX; Reports, Descriptive